Psychological Distress among Ebola Survivors Discharged from an Ebola Treatment Unit in Monrovia, Liberia – A Qualitative Study - Rabelo, Ionara; Lee, Virginia; Fallah, Mosoka P.; Massaquoi, Moses; Evlampidou, Iro; Crestani, Rosa; Decroo, Tom; Van den Bergh, Rafael; Severy, Nathalie (Frontiers in Public Health, 2016)
Introduction A consequence of the West Africa Ebola outbreak 2014-2015 was the unprecedented number of Ebola survivors discharged from the Ebola Treatment Units (ETU). Liberia alone counted over 5000 survivors. We undertook a qualitative study in Monrovia to better understand the mental distress experienced by survivors during hospitalization and reintegration into their community. Methods Purposively selected Ebola survivors from ELWA3, the largest ETU in Liberia, were invited to join focus group discussions. Verbal informed consent was sought. Three focus groups with a total of 17 participants were conducted between February and April 2015. Thematic analysis approach was applied to analyze the data. Results The main stressors inside the ETU were the daily exposure to corpses, which often remained several hours among the living; the patients’ isolation from their families and worries about their wellbeing; and sometimes the perception of disrespect by ETU staff. However, most survivors reported how staff motivated patients to drink, eat, bathe, and walk. Additionally, employing survivors as staff fostered hope, calling patients by their name increased confidence and familiarity, and organizing prayer and singing activities brought comfort. When EVD survivors returned home, the experience of being alive was both a gift and a burden. Flashbacks were common among survivors. Perceived as contagious, many were excluded from their family, professional and social life. Some survivors faced divorce, were driven out of their houses or lost their jobs. The subsequent isolation prevented survivors from picking up daily life, and the multiple losses affected their coping mechanisms. However, when available, the support of family, friends and prayer enabled survivors to cope with their mental distress. For those excluded from society, psycho-social counselling and the survivor’s network were ways to give a meaning to life post-Ebola. Conclusion Exposure to death in the ETU and stigma in the communities induced post-traumatic stress reactions and symptoms of depression among Ebola survivors. Distress in the ETU can be reduced through timely management of corpses. Coping mechanisms can be strengthened through trust relationships, religion, peer/community support, and community-based psychosocial care. Mental health disorders need to be addressed with appropriate specialized care and follow-up.